2011
DOI: 10.1177/109804821101500102
|View full text |Cite
|
Sign up to set email alerts
|

From Web 2.0 to Web 3.0: Implications for Advertising Courses

Abstract: The proliferation of advertising applications facilitated by Web 2.0 technology has changed the way organizations interact with customers. Sites like YouTube and Facebook have caused firms to modify advertising models to take into consideration the value of social media and user-generated content. However, with such content come critical issues about information accuracy, source credibility, and amateurish presentation. Web 3.0 combines human and artificial intelligence to make information richer, more relevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A search of the extensive EBSCOhost Academic Search Premier database in January 2013 found only seven documents about Pinterest, none of which was in the business literature (undoubtedly, they will soon appear). But reports are beginning to appear in blogs and other online sources, and researchers have investigated the pedagogical uses of similar networks (Brown, 2012;Scovotti & Jones, 2011). It has been reported that Pinterest is being used in a media graphics course at the University of Minnesota and in a journalism course at Minnesota State University (Holt, 2012).…”
Section: Get Students Pinterested In Marketing and Advertisingmentioning
confidence: 99%
“…A search of the extensive EBSCOhost Academic Search Premier database in January 2013 found only seven documents about Pinterest, none of which was in the business literature (undoubtedly, they will soon appear). But reports are beginning to appear in blogs and other online sources, and researchers have investigated the pedagogical uses of similar networks (Brown, 2012;Scovotti & Jones, 2011). It has been reported that Pinterest is being used in a media graphics course at the University of Minnesota and in a journalism course at Minnesota State University (Holt, 2012).…”
Section: Get Students Pinterested In Marketing and Advertisingmentioning
confidence: 99%
“…Next, the Web will become even more intelligent compared with the current solutions and will additionally permit the composition of more complex functionality and services by the user (e.g. [8], [9], [10]).…”
Section: Introductionmentioning
confidence: 99%
“…(Kroeker, 2010, p.16) Marketers are therefore faced with the challenge of adapting #-% #$(% )$&01"01% ;(<% &06% /06"01% . (*(5&0)(% in this important sphere (Scovotti & Jones, 2011). These advancing media technologies offer numerous communication opportunities and capabilities to tailor contact strategies and 6(5(*-2% &% 80"/(6% :(,,&1(3% 4$",% $&,% .…”
Section: Introductionmentioning
confidence: 99%